2008
DOI: 10.1097/brs.0b013e318166f58c
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Tuffierʼs Line as an Anatomic Landmark

Abstract: Tuffier's line demonstrated predictable sex-related differences: men had an intercristal line that most often intersected the L4 body or inferior endplate whereas the women's intercristal line most often intersected the L5 body or superior endplate. However, because the actual level of Tuffier's line may vary from the L4 body to the L5 body, the intercristal line is insufficient to use as the sole landmark for assessing spinal segmental level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 17 publications
(26 reference statements)
1
25
1
5
Order By: Relevance
“…[3][4][5] Due to differences related to gender, height, and body mass index (BMI), Tuffier's line has been reported to intersect the vertebral column anywhere from the L3-L4 to the L5-S1 intervertebral discs. [3][4][5][6] In men, Tuffier's line most often intersects the body of L4 or its inferior endplate, whereas in women, it most commonly intersects the body of L5 or its superior endplate. 5 It is imperative to highlight that Tuffier's line is a radiological landmark that does not take into account the patient's body habitus or positioning.…”
Section: Résumémentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] Due to differences related to gender, height, and body mass index (BMI), Tuffier's line has been reported to intersect the vertebral column anywhere from the L3-L4 to the L5-S1 intervertebral discs. [3][4][5][6] In men, Tuffier's line most often intersects the body of L4 or its inferior endplate, whereas in women, it most commonly intersects the body of L5 or its superior endplate. 5 It is imperative to highlight that Tuffier's line is a radiological landmark that does not take into account the patient's body habitus or positioning.…”
Section: Résumémentioning
confidence: 99%
“…[3][4][5][6] In men, Tuffier's line most often intersects the body of L4 or its inferior endplate, whereas in women, it most commonly intersects the body of L5 or its superior endplate. 5 It is imperative to highlight that Tuffier's line is a radiological landmark that does not take into account the patient's body habitus or positioning.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…showed that Tuffier's line demonstrates predictable sex-related anatomic differences with men having an intercristal line that most often intersects the body of L4 or its inferior endplate and with women having the intercristal line most often intersect the body of L5 or its superior superior endplate [7]. And also showed that weight and BMI are not associated with the level of Tuffier's line in this study.…”
Section: Discussionmentioning
confidence: 52%
“…Tuffier's line is a clinical landmark defined as a horizontal line connecting the superior aspect of the posterior iliac crests and commonly used as a reference to localize the L4 vertebral body before performing a lumbar puncture [7]. However Tuffier's line is unreliable in determining the correct lumbar vertebral level.…”
Section: Discussionmentioning
confidence: 99%